Peran Religiusitas terhadap Konformitas pada Mahasiswi Berhijab - Amalia Juniarly; Dira Dahtiarani (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2019)
The study aims to determine the role of religiosity on conformity in hijab female students. The study population was university X students whom wear hijab, and with aged 18-23 years old. The research sample used 160 people and for try out with 50 people. This study used sampling quota techniques. Religiosity and conformity was measured by the scale which refers to the  dimensions of religiosity from Ancok and Suroso (2011) and type of conformity from Nail, Domenico and McDonald (2013). The research used simple regression analysis. The result obtained by value of RR = 0.559, R square = 0.313, F = 71.884, P = 0.000 (p <0.05), it meaning that there is a significant role of religiosity towards conformity. Thus the hypothesis proposed is accepted.